Synchronized Two-Stage Lot Sizing and Scheduling Problem in Automotive Industry - Özdemir, Rifat Gürcan; YÜKSEKTEPE, FADİME ÜNEY (Springer-Verlag Berlin, Heidelberger Platz 3, D-14197 Berlin, GermanySpringer-Verlag Berlin, Heidelberger Platz 3, D-14197 Berlin, Germany, 2012)
This study proposes a mixed-integer linear programming model to solve the synchronized two-stage lot sizing and scheduling problem with setup times and costs. The main motivation behind this study is based on the need of improvement in the inventory control and management system of a supplier that serves to automotive industry. The supplier considered in this study has synchronized two-stage production system which involves three parallel injection machines in the first stage and a single spray dying station in the second stage. In order to achieve synchronization of the production between these stages and improve the inventory levels, a mixed-integer linear programming model is proposed. By the help of developed model, synchronization between the parallel injection machines and the single spray dying station with minimum total cost is obtained. Optimal lot sizes for each stage and optimal schedules of these lot sizes are determined by the developed model as well.